The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/6459276
|View full text |Cite
|
Sign up to set email alerts
|

Friedman Score in Relation to Compliance and Treatment Response in Nonsevere Obstructive Sleep Apnea

Abstract: Nonsevere obstructive sleep apnea (OSA) is most often treated with a continuous positive airway pressure (CPAP) device or a mandibular advancement splint (MAS). However, patient compliance with these treatments is difficult to predict. Improvement in apnea-hypopnea index (AHI) is also somewhat unpredictable in MAS treatment. In this study, we investigated the association between Friedman tongue position score (Friedman score) and both treatment compliance and AHI improvement in patients with nonsevere OSA rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Objective measures of PAP compliance have recently become part of routine clinical practice, and insurance companies now cover reimbursements for the devices and disposable supplies according to the compliance measured by the PAP device itself (Hevener & Hevener, 2016). In contrast, measurement of compliance to OA therapy has relied on self‐reporting in many studies (Berg et al, 2020; Lo et al, 2021; Pahkala & Suominen, 2021) as well as in routine clinical practice. Lowe et al first presented objective evidence of compliance using a monitor with a temperature sensor (Lowe et al, 2000), and additional studies have since reported objective compliance with OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Objective measures of PAP compliance have recently become part of routine clinical practice, and insurance companies now cover reimbursements for the devices and disposable supplies according to the compliance measured by the PAP device itself (Hevener & Hevener, 2016). In contrast, measurement of compliance to OA therapy has relied on self‐reporting in many studies (Berg et al, 2020; Lo et al, 2021; Pahkala & Suominen, 2021) as well as in routine clinical practice. Lowe et al first presented objective evidence of compliance using a monitor with a temperature sensor (Lowe et al, 2000), and additional studies have since reported objective compliance with OA.…”
Section: Discussionmentioning
confidence: 99%
“…Objective measures of PAP compliance have recently become part of routine clinical practice, and insurance companies now cover reimbursements for the devices and disposable supplies according to the compliance measured by the PAP device itself (Hevener & Hevener, 2016). In contrast, measurement of compliance to OA therapy has relied on self-reporting in many studies (Berg et al, 2020 and micro-recorder (DentiTrac ® ; Braebon Medical). In this study, a micro-recorder (DentiTrac ® ) embedded into an OA was used to monitor objective compliance with the OA.…”
Section: Discussionmentioning
confidence: 99%
“…Participants aged ≥ 18 years who were referred to our units for sleep respiratory disorders were enrolled and subjected to clinical diagnostic evaluation and consequently phenotyped. A full clinical history of symptoms, such as morning headache and decreased libido, validated questionnaires (ESS), and anatomical or endoscopic scores were collected ( Table 1 ) ( Supplementary File S1–S3 ) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Drug-induced sleep endoscopy was performed for all the patients. All patients revealed vellum anterior–posterior collapse over 50% and oropharyngeal lateral 50% collapse, reaching the Friedman grade II of lingual tonsils hypertrophy without epiglottic collapse by drug-induced sleep endoscopy (DISE) under the VOTE grading system [ 20 ]. In addition, all patients underwent PSG, which revealed at least moderate and severe OSA.…”
Section: Methodsmentioning
confidence: 99%